Development of Biodegradable Food Packaging Materials from Agricultural Biomass - Bidu, Jerome M; Towo, Arnold; Haule, Liberato; William, Joshua C; Kaale, Lilian D (Tanzania Journal of Science, 2021)
This study utilised maize husk fibres and pulp to prepare a biocomposite fabric for food packaging. The optimum conditions for extracting maize husk fibres were determined experimentally to be 5 g/l of sodium hydroxide concentration at 100 °C for 60 minutes and liquor ratio of 1:20. The fabric was manufactured by solution casting of maize husk pulp on a web prepared by aligning maize husk and sisal fibres using a deckle and frame. The sisal fibre content was varied from 5 to 50% at ratios ranging from 95:5 to 50:50 (maize: sisal fibres). The biodegradable fabric was characterised using three mechanical properties: tear strength, tensile strength, and abrasion resistance. The tear strength ranged from 0.79 MPa to 3.93 MPa whereas the tensile strength ranged from 13.35 MPa to 56.46 MPa, which conforms to the data available from literature. Abrasion tests verified that there was no mass loss at 5,000, 10,000 and 15,000 cycles. Overall, the study findings show that maize husk fibres can replace up to 80% of sisal fibres in materials for food packaging applications without compromising their quality. Keywords: Maize husk fibre, biocomposite, sisal fibres, food packaging.